Proyecto de inversión para la creación de una empresa de confección y comercialización de uniformes para dotación empresarial elaborados con textiles ecológicos, en la ciudad de Armenia. (2013)
This Investment project shows an offer to establish an enterprise that can contribute to the region development. Starting of business new strategies, with the objective to Incentive the population to buy ecological products. The work Is based on theoretical argument, by means of marketing studies realization, by which the answers obtained were very positive from potential marketing and comes from the established mipymes of Department of Quindío, and the used tool was Survey. According to the previous It Is to proceed to work on the technical study, that permited to know a whole procedure from the distribution of the plant until the delivery of the product, sameway in the admistrative study It was projected an style that warrants the right conservation and optimization of resources, to manage the staff correctly and the generation of Income That allows reinvestment and support. Also It was noticed the different variables that corresponds to the financial study and that allowed to know It´s evaluation toward a waited opportunity rate by the Investors, The TiR, The VPN, the relationship, benefits cost. (VPB/VPC) Indicators that showed their low rates In growing matter. In conclusion and according with the different studies made, It´s reflected a clear opportunity of marketing, not only for the region development, but also to Impose new standars of the Industry products and the consumers behavior at obtaining a ecological product. It is recommended to analyze the financial evaluation data to Improve new strategies that allow to take advantage of the opportunity of marketing, existing In the Department of Quindío.